Content analysis of Manila Bulletin, Philippine Daily Inquirer and the Philippine Star and their relationship to the public perception on the interior design - Ubana, Michelle Marie M.; Buencamino, Lorena M. (2008.)
This study examined local newspaper articles on interior design to determine the prevailing topics published during the time of the study. It intended to analyze the contents of the articles and evaluate them to determine if they correspond with the readers' perception of interior design. The fundamental methods used in the study were the content analysis of the newspaper articles and survey method to find out the readers' perception. A purposive sampling method was used in the selection of the leading Philippine broadsheets, which have interior design articles namely, Manila Bulletin, Philippine Daily Inquirer, and The Philippine Star. On the other hand, the incidental method was applied in picking out 50 respondents surveyed in the first three consecutive weekends of February 2008. Respondents in the survey were those who read interior design articles published in the sampled broadsheets for at least five years. Results of the study showed that the common topics of the articles included product or company advertisements such as real estate, construction materials, and furniture companies, and information on interior design. There was sixty percent commonality between the results of the content analysis of newspaper articles and survey results from readers' perception. The forty percent disparity can be attributed to the fact that the respondents have been exposed to other mass media such as design magazines, television, and the internet offering them other perceptions on interior design other than those from the broadsheets.
Thesis (BSID)--University of the Philippines Diliman
Keywords: Newspapers -- Sections, columns, etc. -- Interior decoration